Regional Characteristics of Precipitation in the Nanpan River Basin, China - Qin, Xinlong; Wang, Long; Li, Xuehui; Yu, Hang; Wang, Kui; Fan, Defang (Frontiers in Environmental Science, 2022)
Nanpan River is the source of the Pearl River in China, and thus, the exploitation of water resources in the Nanpan River Basin directly affects development in its middle and lower reaches. In the present study, the availability of water resources in the Nanpan River Basin and their differences were investigated. Sixteen statistical variables including the 25th and 75th percentiles, the coefficient of variation of the seasonal and annual precipitation and the annual precipitation concentration index were examined using monthly precipitation data collected in 33 stations in the Nanpan River Basin from 1956 to 2016. This paper studies the relationship between the Spearman’s rank correlation coefficient and the distance between stations, and uses principal component analysis (PCA) and cluster analysis to identify the homogeneous precipitation regions in the Nanpan River Basin. The results reveal the following: 1) The Spearman’s rank correlation coefficients for the monthly, seasonal and annual precipitation of the stations exhibit negative correlations with the interstation distance; the stronger the spatial correlation between both parameters, the shorter the time scale. 2) The factors controlling the spatial patterns of precipitation in the basin are its interannual and intra-annual variations. 3) Precipitation for the Nanpan River Basin produce two homogenous regions, which are associated with the influences of the South Asian monsoon, the North Atlantic Oscillation and the South Branch Trough. The first region is mainly to the east of longitude 104°E, while the second is principally to the west.